The Effect of Training, Competence and Work Motivation on Employee Performance - Nurlaely Razak (Jurnal Economic Resource, 2021)
This study aims to explore the effect of training, competence, and work motivation on employee performance. This study was conducted at the Provincial Education Office of South Sulawesi. The population of this study consisted of employees of the Province of South Sulawesi's Education Office. These criteria applied to 363 employees. The distribution of questionnaires accomplished data collection to all respondents. Numerous stages of testing, such as tests, were used to assess the data (validity, reliability, normality, heteroscedasticity, multicollinearity). Additionally, the hypothesis is tested using multiple regression and the coefficient of determination test and the partial test (t-test) and simultaneous test (f-test). The findings indicated that training, competence, and work motivation variables had a favorable and substantial effect on employee performance at the Education Office of South Sulawesi Province, either concurrently or partially. The results indicated that among the three independent variables used to determine the level of influence on employee performance, the training variable had the most impact on enhancing employee performance at the South Sulawesi Education Office.